Senescence-Induced Atherosclerosis: The Potency of Senolytic Therapy - Ratih, Udani Sari; Iswanti, Febriana Catur (HM Publisher, 2024)
The aging process is an inevitable occurrence that involves physiological changes at the cellular level. The presence of intrinsic and extrinsic stressors can cause cellular damage, leading to senescence and premature aging. Senescent cells undergo activation of the p53/p21 and p16INK4a pathways, induce cell cycle arrest, increased expression of senescence-associated beta-galactosidase (SA-β-Gal), and secretion of SASP (senescence-associated secretory phenotype), leading to